Folsom : new archaeological investigations of a classic Paleoindian bison kill - Meltzer, David J.; Balakrishnan, Meena (Berkeley : University of California Press, 2006)
Annotation The first comprehensive analysis of the original excavations (c. 1920s) and more recent archaeological and ecological research conducted at the Folsom, New Mexico bison hunting site, which established the Pleistocene antiquity of humans in North America and defined the Folsom paleoindian culture.
Introduction: The Folsom Paleoindian site -- Folsom and the human antiquity controversy in America -- Situating the site and setting the ecological stage -- Archaeological research designs, methods, and results -- Geology, paleotopography, stratigraphy, and geochronology -- Late glacial climate and ecology -- The faunal assemblage and bison bonebed taphonomy -- Artifacts, technological organization, and mobility -- Folsom, from prehistory to history -- Appendix A: Field procedures and protocols -- Appendix B: The Folsom diary of Carl Schwachheim -- Appendix C: Historical archaeology of the Folsom site -- Appendix D: Sediment mineralogy and bone preservation -- Appendix E: Defining Folsom: theme and variations.
Includes bibliographical references (pages 345-366) and index.
106574
Keywords: Folsom culture -- New Mexico -- Colfax County; Folsom points; Excavations (Archaeology) -- New Mexico -- Colfax County; Animal remains (Archaeology) -- New Mexico -- Colfax County; Culture de Folsom -- Nouveau-Mexique -- Colfax; Pointes de Folsom -- Nouveau-Mexique -- Colfax; Fouilles (Archeologie) -- Nouveau-Mexique -- Colfax; Restes d'animaux (Archeologie) -- Nouveau-Mexique -- Colfax; Indiens du paleolithique -- Nouveau-Mexique -- Colfax; Folsom Site (N.M.); Colfax County (N.M.) -- Antiquities